A magnitude scale for cascading disasters. (September 2018) - Alexander, David
Abstract: This paper presents a magnitude scale for cascading incidents, crises and disasters. The scale is listed, described and discussed in terms of its possible applications. A graphic form is presented as well as a tabular one. Examples are discussed in order to illustrate the different levels of the scale. The need for the scale is described in relation to evolving trends in research on cascading disasters, especially in terms of the cross-sector implications of critical infrastructure failure. By facilitating comparison between events, the scale may be able to help planners transfer knowledge and lessons from one cascading disaster to another, or to a situation in which one is likely. Future development of the scale might involve creating a quantitative means of applying it, connecting it to other scales designed to measure or assess disaster impacts and using it to understand the broader implications of infrastructure management decisions.